A Study of Ge Mai's Poetry in the Context of Christian Culture - LIU , Junjun (Journal of Research for Christianity in China (JRCC), 2025)
In contemporary Chinese poetry studies, research on Ge Mai's poetry has long been undervalued. This paper primarily examines Ge Mai's poetry within the context of Christian culture. Although some critics have offered relatively systematic interpretations of Ge Mai over the years, detailed textual analysis has been lacking. Building upon previous research, this paper attempts to reinterpret Ge Mai's poetry and the poet himself from a religious and cultural perspective. The article argues that for certain writers, the roots of modern Chinese poetry in Western culture run deeper than its connections to classical Chinese poetry. The Bible, a classic of Western religious culture, became a significant poetic resource for the poet Gomei. His poetry employs a subtle poetic transformation of biblical themes. To some extent, Gomei's poetic journey can be seen as an artistic life, bearing certain similarities to the faith of saints. The complexity of the poet's own character, coupled with a lack of transcendental dimension in his experience of religion (and poetry), ultimately led Gao Mei to self-negation and a descent into the abyss of nihilism—turning the notion of “art saving life” on its head.
Keywords: Ge Mai Poetry Christianity